Monsters to destroy: understanding the war on terror - Bapat, Navin A. (Oxford scholarship online Political Science, 2019)
This study argues that the war on terror can be explained as an effort to cement the U.S. dollar as the world's foremost reserve currency by expanding American control over the global energy markets. Since the 1970s, the states of OPEC agreed to denominate their oil sales in U.S. dollars in exchange for American military protection. The 9/11 attacks gave the U.S. cover to eliminate current challengers to this system while simultaneously striking new security agreements with host states throughout the Middle East, Africa, and central Asia that are critical to the extraction, sale, and transportation of energy to global markets. However, the U.S. security guarantee soon created a moral hazard problem. Since the host states had American protection, they were free to engage in corrupt behaviours - while labeling their political opponents as terrorists.